Gambaran anatomi dan histologi oesofagus dan proventrikulus pada ayam hutan merah (Gallus gallus) asal Pulau Timor - Aplonia Brigita Yulia Teme; Yulfia N Selan; Filphin A. Amalo (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
This research aims to describe Macroscopic and microscopic oesophagus and proventriculus the red jungle fowl (Gallus gallus) from the island of Timor. The main material used in this study a piece of tissue 6 pieces esophagus and proventriculus. Chicken killed by create air embolism into the heart using a spuit through the chest cavity, continue taken organ oesophagus and proventriculus to perform microscopic. further cuts and fixation of tissue samples. Tissue that have fixed taken for preparation of histology. The results showed that esophagus divided into cranial, medial and caudal. with a total rerata length 13,3 ± 3,74 cm, weight 5,2 ± 0,21 g, diameter cranial 0,3 ± 0,0 mm, diameter medial 0,1 ± 0,0 mm and diameter caudal 0,2 ± 0,0 mm. Esophageal mucosa covered by epitelium squamosum compleks not keratinized, and consists of lamina propria and muscularis mucosa. Esophageal gland-type mucus, found in abundance distribution along the esophageal mucosa. Submucosal startum consisting of loose connective tissue. The external muscular startum consisting of the inner circular smooth muscle and longitudinal smooth muscle on the outside. and adventitia layer composed of blood vessels and loose connective tissue. Proventrikulus has a total rerata length of 2,5 ± 0,0 cm, weighs 1,6 ± 0,1 g and a diameter of 0,7 ± 0,0 mm. Startum consisting of lamina epithelialis mucosa, lamina propria, and muscularis mucosa. Submucosal startum in the form of connective tissue. Tunica muscularis satrum composed by smooth muscle. Serous tunica startum consists of loose connective tissue and mesothelium